2008
DOI: 10.1136/emj.2007.047068
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotic syndrome presenting as deep vein thrombosis or pulmonary embolism

Abstract: A patient presenting with a swollen left leg and pleuritic chest pain was shown to have deep vein thrombosis (DVT) by Doppler studies. He was anticoagulated but required two further admissions with swelling of both legs before a diagnosis of nephrotic syndrome was considered and confirmed. Renal biopsy showed that this was caused by membranous nephropathy. Two audits were subsequently conducted. The first was of diagnostic discharge codes for nephrotic syndrome and venous thromboembolism in south west Scotland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 8 publications
2
9
0
Order By: Relevance
“…In our case, pulmonary embolism was the first presenting feature of the nephrotic syndrome. It was even reported by Hartland et al [6], Peces et al [7] and Ambler et al [8]. No other site of thrombosis was detected in our patient.…”
Section: Discussionsupporting
confidence: 75%
“…In our case, pulmonary embolism was the first presenting feature of the nephrotic syndrome. It was even reported by Hartland et al [6], Peces et al [7] and Ambler et al [8]. No other site of thrombosis was detected in our patient.…”
Section: Discussionsupporting
confidence: 75%
“…However, multivariate analysis showed mixed DVT was not a risk factor for DVT relapse. The fact that patients with concomitant diabetes, SLE, or NS are more likely to develop DVT has been widely accepted [3133]. Univariate analysis showed the incidence of DVT relapse in patients with these internal diseases was about 1.5 times higher than that in other patients, but in regression analysis these diseases had no influence on the DVT relapse ( P diabetes =0.298; P SLE =0.076; P NS =0.090).…”
Section: Discussionmentioning
confidence: 99%
“…This is based on several case studies and retrospective studies [8][9][10][11]. One retrospective study demonstrated that patients with nephrotic syndrome are more than twice as likely to develop DVT compared to the non-nephrotic population [11].…”
Section: Introductionmentioning
confidence: 99%